Feasibility studies and system performance of 2 MW solar PV plant at UTeM - Abunima, Hamza Z. M. (2015)
Photovoltaic (PV) is becoming increasingly important as one of the most promising source of renewable energy to tackle climate change challenge. Four PV systems were installed in UTeM, namely polycrystalline, thin film, HIT, and monocrystalline with total capacity of 23.88 kW. In this regard, this research aims to evaluate the complete electrical design of a 2 MW grid-connected solar PV plant located in UTeM, Melaka. To achieve this, a site survey was carried out to inspect the installation site condition as well as the distance to the possible interconnection point. In addition, meteorological parameters were obtained from Meteonorm software. The existing PV systems in UTeM were used to export actual meteorological data at the proposed site. Subsequently, the PV modules orientation, array sizing, and cable sizing were determined based on the data obtained. Inverters and transformers for this PV plant were proposed and studied. The research highlights the key factors that affect the performance of solar PV power systems. Furthermore, the performance ratio and specific yield of the proposed plant were calculated to verify the plant design validity. Economic viability was also analyzed based on the system performance. It take into account the Feed-in Tariff (FiT) scheme. Financial models of the project were assessed and expressed as levelized cost of energy, simple pay back, internal rate of return, and present value of the net profit. The key findings suggest that the project has economic and environmental value which is socially beneficial to the community in Melaka state. The proposed solar PV plant is expected to generate an annual energy of approximately 2,395 MWh, with return on investment of 13.7%. Therefore, the proposed 2 MW solar PV power plant is technically and economically feasible.